Promoting realistic learning in teacher training through metaphorical resources (2018)
Professionalization is the most important part in teacher training to achieve the educational quality needed in basic education. In this article, we present the main results of a research on realistic training in a master’s program in preschool education with professional orientation, where the use of metaphor as an instrument of formative analogue assessment is highlighted. This study is located in an evolutionary interventionist paradigm, qualitative cut. The instruments for obtaining data were: audio recordings and transcriptions of the main events of the class, written reflections and thematic portfolios of the students. The research was conducted with two groups of the master’s degree in preschool education, during a school year. The results show that the use of metaphoric resources allows the students’ prior knowledge to emerge and build on the anchoring with new knowledge, within a reflective formative process. The analogical evaluation constitutes a means for the expression of knowledge and emotions that allows the awareness of the teachers in formation about the own evolution.